Penerapan Sistem iLearning Raharja Ask And News (iRAN) Dalam Mendukung Media Informasi Kampus Pada Perguruan Tinggi Raharja - Untung Rahardja; Dina Fitria Murad; Bunga Pertiwi (CCIT Journal, 2014)
Media information developed so rapidly in line with technological developments. Media information running on a college, greatly affects the student in understanding the developments taking place in its environment. Application of the media aims to facilitate students in meeting the needs of science. However, the use of the information media and the campus is not optimal yet computerized student ignorance will lead to the existence of such media. Thus the importance of online information media to facilitate the process of information retrieval. Now with iLearning learning, all the information can be integrated extensively. iRAN is a campus information media that have been computerized aims to manage all documentation of an event, incident, and campus information. In this case to measure the quality of information produced, iRAN adopted a study conducted by DeLone and McLean (1992) showed that among the six categories that build on the success of information systems, there is a connection and dependence which then determine the success or failure of the implementation of an information system. In addition there are 6 literature reviews that can be used as references in preparing this report. The final result of the study is an integrated information system that is widely campus, where iRAN can provide the latest information about activities or events that are taking place within the campus while also every student can participate share what they know into iRAN.